Perception of Rural Malaysian Women Leaders on Their Input Into the Process of Decision Making in Farmers Organizations - Khaled, Mohamed (1997)
The major objective of this study was to explore the involvement of rural Malaysian women in the process of decision making in rural farmers organizations. The major objective of the study was to examine the participation of rural Malaysian leaders in decision making in elation to their empowerment and share of power at societal level. The specific objectives were: (a) to examine the socio':'demographic, economic, and leadership characteristics of rural women leaders in rural/farmers organizations, (b) to examine the levels of participation of rural women as members and leaders in rural/farmers organizations, (c) to examine rural women leaders' perception on decision making inputs in rural farmers organizations, (d) to determine the factors that contribute to rural women leaders perception on decision making inputs and, to (e) to identify the gender based inequalities, institutional and organizational constraints that hinder women's participation in decision making.Farmers Organizations' Authority (FOA) a nation wide farmers organization was selected as the case study. Both quantitative and qualitative approaches were used to encompass the objectives of the study. The secondary data showed that even though women constitute 21 percent of the membership of the organization, but their representation as leaders consist only 6 percent. A combination of personal, characteristics gender and institutional/organizational factors were found to be behind their low representation as leaders. The study hypothesised nine predictor variables of the personal characteristics to affect women's perception on their decision making inputs. Only age was found to have a significant effect at pc 0.05. The study suggested the gender factors as deep rooted within the cultural set up of the society and their transcendence is a long term process related to changes of the value systems of the society. Hence the organizational and institutional factors are seen to be the potential subject of short term actions to overcome the reality of women's low representation in rural farmers' organizations. Among other recommendations, gender sensitization of policy makers was suggested as a priority to effect institutional and organizational change. It was concluded that the coalition of market/business oriented policies together with the patriarchal mode of production have contributed to further subordination of rural Malaysian women in the aftermath of traditional agricultural production.